Interstitial lung disease - Vincent Cottin (European Respiratory Review, 2013)
This article reviews the most important articles published in interstitial lung disease, as reviewed during the Clinical Year in Review session at the 2012 annual European Respiratory Society Congress in Vienna, Austria. Since the recent international guidelines for the management of idiopathic pulmonary fibrosis (IPF), important new evidence is available. The anti-fibrotic drug pirfenidone has been recently approved in Europe. Other pharmacological agents, especially nintedanib, are still being tested. The so-called triple combination therapy, anticoagulation therapy and endothelin receptor antagonists, especially ambrisentan, are either harmful or ineffective in IPF and are not recommended as treatment. Although the clinical course of IPF is highly variable, novel tools have been developed for individual prediction of prognosis. Acute exacerbations of IPF are associated with increased mortality and may occur with higher frequency in IPF patients with associated pulmonary hypertension. Interstitial lung disease associated with connective tissue disease has been definitely established to have a better long-term survival than IPF. A subset of patients present with symptoms and/or biological autoimmune features, but do not fulfil diagnostic criteria for a given autoimmune disease; this condition is associated with a higher prevalence of nonspecific interstitial pneumonia pattern, female sex and younger age, although survival relevance is unclear.